Cultural Wisdom and Character Building in Islamic Boarding Schools: A Case Study in Madura - Sarwan, Sarwan (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This article aims to describe the cultural wisdom of Madura and its internalization process in the educational process at the Miftahul Ulum Islamic Boarding School, Bette Village, Pamekasan, Madura. Gap research and novelty in the research are specifications of Madurese cultural values that focus on forming students' character. This research is qualitative research with a case study approach. The data sources in this study were the principal, two ethical study teachers, and one guidance and counseling teacher. Data collection techniques used in-depth interviews, participatory observation, and documentation studies. Data analysis used data reduction, data presentation, and conclusion stages. Data validity was strengthened by method triangulation and confirmability. Based on the discussion of the research results, the cultural values internalized in the educational process at the Miftahul Ulum Islamic Boarding School are being devoted to parents, respecting the elders and loving the younger ones, becoming individuals who care, are responsive, and are ready to assist others.